Intellectual Property And Ownership - Mohnani, Aryan (Trinity Law Review, 2021)
The world is continuously being technologically advanced, whether it is in medicine or  business. Humans have been utilizing and making the most value of their ideas and thoughts.  As we live in this dynamically fast-paced world, we need to ensure that the products of human  intellect aren’t being pinched and stolen away. This is when Intellectual Property comes to  mind. These can be protected by the law so that the valuable thoughts and ideas of the  individual are nourished and awarded, either by financial or general recognition. Huge  companies like Microsoft to Sony, all make sure that their designs and inventions are protected  and they do that by registering them as Intellectual Properties. That’s why it is crucial to learn  more about Intellectual Property and its rights.
Keywords: Ownership; Intellectual Property; financial or general recognition